Finite-time stabilization for fractional-order inertial neural networks with time varying delays - Aouiti, Chaouki; Cao, Jinde; Jallouli, Hediene; Huang, Chuangxia (Nonlinear Analysis: Modelling and Control, 2022)
This paper deals with the finite-time stabilization of fractional-order inertial neural network with varying time-delays (FOINNs). Firstly, by correctly selected variable substitution, the system is transformed into a first-order fractional differential equation. Secondly, by building Lyapunov functionalities and using analytical techniques, as well as new control algorithms (which include the delay-dependent and delay-free controller), novel and effective criteria are established to attain the finite-time stabilization of the addressed system. Finally, two examples are used to illustrate the effectiveness and feasibility of the obtained results.
Keywords: inertial neural networks; finite-time stabilization; fractional-order system; Caputo fractional derivative and integral